2011
DOI: 10.1177/2151458511430662
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation (ORIF) of Complex 3- and 4-Part Fractures of the Proximal Humerus

Abstract: Introduction: Treatment of complex fracture patterns of the proximal humerus continues to be a challenging and controversial clinical scenario. The aim of this study was to report on the outcomes of complex displaced 3-and 4-part fractures of the proximal humerus treated with locked plating and compare the functional results of patients on the basis of age at time of injury. Methods: A retrospective review was completed to identify patients whom had sustained a 3-or 4-part fracture of the proximal humerus (Nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
(46 reference statements)
0
9
0
1
Order By: Relevance
“…In our study we had one patient with avascular necrosis which was diagnosed at sixth month followup. The incidence of AVN varies from 0-68% throughout the literature 30,31 .The fracture type itself, the length of the dorsomedial metaphyseal extension, and the integrity of the medial hinge were found to be the most relevant predictors of humeral head necrosis. This is supported by the a study by Jost et al 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study we had one patient with avascular necrosis which was diagnosed at sixth month followup. The incidence of AVN varies from 0-68% throughout the literature 30,31 .The fracture type itself, the length of the dorsomedial metaphyseal extension, and the integrity of the medial hinge were found to be the most relevant predictors of humeral head necrosis. This is supported by the a study by Jost et al 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown no difference in outcomes between elderly patients and younger patients following surgical fixation of proximal humerus fractures. 25 - 27 Further, a 1-year outcome study of 637 proximal humerus fractures showed that social independence, not age, was a predictor of outcome. 19 …”
Section: Evaluation and General Considerationsmentioning
confidence: 99%
“…Threeand four-part fractures in patients who are younger than 40 should almost always be treated with ORIF or PF. Contrary to this opinion, Grawe et al (2012) demonstrated good outcomes in elderly patients treated with ORIF in three-and four-part fractures although they did not list complications as it related to patient age. At this time, these patients may be better treated with reverse shoulder arthroplasty or, if bone quality and healing potential is good, a hemiarthroplasty (Wiater and Fabing, 2009).…”
Section: Surgical Decision Makingmentioning
confidence: 63%